The Bloody Board Game: A Game-Based Approach for Learning High-Value Care Principles in the Setting of Anemia Diagnosis - Thomas John Pisano; Valeria Santibanez; Marcelo Hernandez; Dipal Patel; Georgina Osorio (Association of American Medical Colleges, 2020)
Introduction With growing health care costs, high-value care is an increasingly important subject for medical training. Many resident and medical student curricula have incorporated lectures-based material about this topic. However, practical-type experiences are needed to refine critical-thinking skills essential for high-value care. Methods To provide such practical experiences, we developed an instructional game for resident-level education that incorporated cost-constraint-based approaches in the workup of anemia. To play the game, teams of learners were given patients with anemia of unknown cause. To pay for their diagnostic tests of choice, teams earned money by correctly answering internal medicine resident-level anemia questions. The first team to successfully work up and diagnose three patients won. Results Resident learners had very positive reviews of our game. As a team, groups of residents across all levels were able to develop cost-effective strategies for diagnosis. Our game also served as a resource for anemia education. Residents on average felt the game enhanced their ability to apply medical knowledge and clinical reasoning (M = 4.7 out of 5, where 5 = strongly agree), as well as high-value care (4.6), and should remain in the program for the high-value care curriculum (4.9). Discussion Game-based learning provides a fun, orthogonal approach to learning critical-thinking skills used during anemia diagnostic patient workups. Although we did not quantify change in diagnostic test ordering, according to resident-learners, our high-value care game improved their ability to integrate cost-effective strategies into their practice of medicine.